The Different of Box Jump, Burpee, and Tuck Jump Exercise Effects to Enhance Power of Leg Muscles and Speed - Khoirul Rifki Saputra (Journal of Sport Science and Education, 2019)
This research aims to analyze the influence of difference exercise box jump, burpee, and tuck jump to power against the limb muscles and speed. Fifty-two students were selected according to criteria will be done pretest to determine the Division of the group by means of ordinal pairing. The process of retrieval of data is done with the test power limb muscles using Jump DF and speed tests using a 30-meter sprint at the time of pretest and posttest. Given the form of exercise for 6 weeks for each group and treatment 3 times in one week. The research results obtained is the percentage increase in limb muscles power of 11% and the speed of 2% on box jump exercises greater than a third group to another. It can be concluded that there are significant effects caused by box jump, burpee and tuck jump exercises to increased power and speed of limb muscles as seen from the test sample paired t-test and there is a difference significant influence between exercises and box jump, burpee and tuck jump to increased power and speed of limb muscles as seen from MANOVA test.